Academic Rankings as a Source of Information for Study Candidates - Pietrzak, Piotr; Cieciora, Małgorzata (Journal of Public Governance, 2021)
Objectives: The aim of the article is to present a proposal for a ranking of public universities in Poland, taking into account the position of their graduates on the labour market. Research Design & Methods: Three reflective indicators were used to create the ranking: average time (in months) from obtaining a diploma to taking up the first job under a contract of employment by graduates; the relative unemployment rate of graduates in the fifth year after graduation among graduates with no work experience prior to graduation; the relative wage rate of graduates in the fifth year after graduation among graduates with no pre-graduation work experience. The structure of three indicators has been based on zero-unitarisation. Findings: The leading universities in the ranking were technical and economic universities. Their 2014 graduates (in all the variety of fields of study offered by these universities) found a job relatively quickly – i.e. within five years of obtaining their diploma – as well as experienced less than average unemployment in the poviats of their residence and their earnings were higher than the average in the poviats of their residence. Implications / Recommendations: It is advisable to continue research on the methodology of creating academic rankings (including reflective indicators). In this regard, it is worth taking into account possibly large – but at the same time homogeneous – research samples. Contribution / Value Added: Extended research on how to create academic rankings (in particular devoted to study candidates). Article classification: research article JEL classification: A23, I23